2020
DOI: 10.1038/s41598-020-59706-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic analysis of unilateral versus bilateral instrumented one-level lateral lumbar interbody fusion

Abstract: Lateral lumbar interbody fusion (LLIF) is a widely applied and useful procedure for spinal surgeries. However, posterior fixation has not yet been decided. We compared the radiographic and clinical outcomes of unilateral versus bilateral instrumented one-level LLIF for degenerative lumbar disease. We conducted a prospective cohort study of 100 patients, who underwent unilateral (group U) or bilateral (group B) instrumented one-level LLIF for degenerative lumbar disease. Forty-one patients in group U were under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…The calculated mean kappa coefficient value for the interobserver reliability was 0.91, and the intraobserver reliability after 8 weeks was 0.94. This represents near perfect agreement between the observers and the time points based on Landis and Koch's measurements [15].…”
Section: Asdsupporting
confidence: 66%
See 1 more Smart Citation
“…The calculated mean kappa coefficient value for the interobserver reliability was 0.91, and the intraobserver reliability after 8 weeks was 0.94. This represents near perfect agreement between the observers and the time points based on Landis and Koch's measurements [15].…”
Section: Asdsupporting
confidence: 66%
“…Subsidence was measured from standing neutral lateral radiographs with parallel end-plates at the index level. The degree of the vertebral body collapse around the disc space was categorized according to the grading system first described by Marchi et al: grade 0, 0-24% collapse; grade I, 25-49% collapse; grade II, 50-74% collapse; and grade III, 75-100% collapse [14,15]. Radiographic ASD in the TLIF group was defined as follows: (1) development of spondylolisthesis of >4 mm, (2) segmental kyphosis of >10 • , and (3) adjacent disc collapse [16].…”
Section: Laboratory Profiles and Radiographic Assessmentmentioning
confidence: 99%
“…The added instrumentation in LLIF is to further reduce motion and increase a construct’s ability to aid in fusion [ 19 ]. The optimal supplemental instrumentation for LLIF had been evaluated by many prior biomechanical and clinical studies [ 4 , 20 , 21 ]. In a three-dimensional finite element study of comparing the kinematic stability afforded by stand-alone cages with those supplemented by lateral plate as well as unilateral or bilateral pedicle screw/rod in a multilevel LLIF construct with simulated osteoporosis, the authors reported stand-alone cage (10–75.1% ROM reduction) and lateral plate (23.9–86.2% ROM reduction) provided inadequate ROM restriction for the multilevel LLIF constructs, whereas lateral cage with BPS (66.7–90.9% ROM reduction) or UPS (45.0–88.3% ROM reduction) fixation provided favorable biomechanical stability [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…UPSF provides biomechanical stability similar to BPSF in post-fusion level 1 TLIF ( 37 ). Currently, the consensus among clinicians is that UPSF should be limited to single-segment posterior lumbar interbody fusions rather than extending to multi-segment fusions due to insufficient fixation strength ( 32 , 38 ). However, due to the lack of evidence of complications such as cage subsidence and adjacent segment disease, as well as the inherent asymmetry and reduced strength of this system, the use of unilateral instruments may result in disconnection, metal failure, or cage migration ( 39 ).…”
Section: Discussionmentioning
confidence: 99%